Pengembangan Sistem Informasi Pengelolaan Konferensi Internasional Universitas Negeri Malang dengan Menggunakan Metode Waterfall - Wibawa, Aji Prasetya; Diantoro, Markus; Idris, Idris; Purnomo, Agus; Kurniawan, Novian Candra (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
An international conference is an event that involves researchers from around the world. This will certainly provide a broader view of the knowledge gained. Problems with the information system managed by the organizer. This problem will certainly hamper the productivity of the organizers. Therefore, the focus of this development is to provide convenience for organizers in conducting conference management that is being held. The method used in this research is waterfall using 4 stages, namely analysis, design, coding, and testing.  The selection of the waterfall method is because the stages in the waterfall are systematic in sequence. This certainly makes it easy for developers to create information systems. The results of this development resulted in an application entitled International Conference State University of Malang "ICON-UM". Based on the results of black-box testing, it is interpreted that all functions developed run optimally. This system can be a recommendation for international conference organizers.